Commentary: A Portrait of the Creative Process in Children’s Learning (LEARNing Landscapes, 2012)
In this filmed interview, Zenia Dusaniwsky describes her first teaching assignment in South America over 20 years ago and how she eventually became the art teacher at St. George’s Elementary School in Montreal. She believes that all children can learn, but not necessarily at the same pace or in the same way. She stresses it is important to "highlight mistakes and failures…not as an endpoint but as part of the process."Moreover, she feels that creativity is as critical as literacy in fostering the overall development of students and their ability to take on future life challenges. She concludes by presenting some of her students’ creative art projects.
Keywords: interview; teaching; art teacher; process; creativity; art